Kaposi's varicelliform eruption in a patient with darier's disease: A rare case report - Trishala Shirahatti; H Bangaru (Wolters Kluwer Medknow Publications, 2024)
Darier's disease is a rare autosomal dominant disorder, characterized clinically by the appearance of multiple, pruritic, discrete, and scaly papules affecting seborrheic areas coupled with palmar pits, nail changes, and mucosal involvement. Histologically, the lesions show supra-basal clefts with acantholytic and dyskeratotic cells. Kaposi's varicelliform eruption (KVE) is the dissemination of the herpes simplex virus in the setting of preexisting skin disease, presenting with disseminated vesico-pustules. Darier's disease presenting as KVE is a rare occurrence. If misdiagnosed or left untreated can increase the rate of mortality. Here, we report the case of a 25-year-old male patient who presented with multiple vesicles and crusted lesions over the face, neck, chest, and upper back. After thorough cutaneous examination, he was found to have multiple hyperkeratotic, dirty-warty papules over seborrheic areas, present since childhood. With detailed clinical and laboratory evaluation, we arrived at the diagnosis of KVE with underlying Darier disease.